Studies on Novel Bisaryl hydrazino-s-triazine Derivatives - J. A. Chaudhari; M. V. Hathi; R. P. Patel (E-Journal of Chemistry)
Various 2-phenyloxy-4,6-bisarylhydrazino-1,3,5-triazines(3a-f) were prepared by reaction of 2- phenyloxy -4,6-dichloro -1,3,5-triazine and various aryl hydrazine derivatives. All the 3a-f derivatives were characterized by elemental analysis and IR spectral studies. All the compounds were screened for microbial activity against gram-positive and gram-negative bacteria.